Long-term variations in trophic groups of coral reef fishes in the lagoon of Meiji Reef in the South China Sea - Zhang, Jun; Gong, Yuyan; Cai, Yancong; Yang, Yutao; Chen, Zuozhi (Frontiers in Conservation Science, 2023)
Fishes play significant ecological functions though many ways in coral reef, and feeding process is one of the most important. To understand responses of reef fish communities to external disturbances, we studied variations in trophic groups of fishes in the lagoon of Meiji Reef in the South China Sea based on fish specimens collected by hand-line and gillnet in 1998—2018, databases and literatures. Differences in species richness, abundance, weight and size of fish in different trophic groups among years were analysed, especially herbivorous and high-economy fish. The results indicated that the percentages of species number and weight of herbivores, piscivores and detritivores decreased significantly from 1998—1999/2016—2018. Herbivorous fishes saw the biggest decline. In the gillnet surveys, the percentages of species number and weight of herbivorous fishes in 1999 were 33.33% and 56.14%, respectively, while the percentages in 2016—2018 were all zero. The species number percentage of large-sized fishes (maximum total length ≥ 65 cm) in 1998—1999 was significantly larger than that in 2016—2018. Thirty-two fish species being found in the lagoon of Meiji Reef during 1998—1999 were not discovered during 2012—2018. Contingency table analysis showed that the disappearance of fish was not significantly related to the vulnerability or resilience of fish rather than economic value. The mean body weight of very high & high-value fish in 1998—1999 was significantly larger than that in 2016—2018. Simple linear regression showed that coral cover had the greater effect on the species number and weight of herbivorous fishes as compare to fishing power. Both fishing power and coral cover had significant effects on the mean body weight. To protect fish on Meiji Reef, we propose to strengthen the conservation initiatives (e.g., creating protected areas, prohibiting fishing, and reconstructing habitat).